Analisis Strategi Bersaing PT. Belfoods Indonesia - , Shanti Widiawati, ST ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Business competition is characterized by the condition that the future full of challenges and uncertainties. Companies need to know the strengths and weaknesses of competitors and other external factors in formulating the right strategy with the TOWS analysis to determine the internal state of the company. PT. Belfoods Indonesia is the first nugget manufacturer in Indonesia and is now experiencing a very drastic decline. To face competition in the frozen food industry, especially with raw materials processed chicken. Availability of various types of processed foods made from raw chicken, both marketed by PT. Belfoods Indonesia as well as those marketed by other companies has caused the competition to win consumers. Therefore, the management company needs to know the strengths and weaknesses of competitors and other external factors in formulating the right strategy. PT. Indonesia Belfoods resources also need to know which ones could be a business advantage by doing a TOWS analysis to determine the internal state of the company. The biggest competitor is PT. Santori Japfa Indonesia (product So Good) and PT. Charoen Pokphand Indonesia (Fiesta products). Alternative strategies that can be formulated in Threats Opportunities Weakness Strength (TOWS) matrix, such as: SO Strategies to increase the production of the most desirable customers, utilizing the distribution channels Sierad Produce for business development and improve the innovation of product development (product diversification). ST strategy to expand into the export market segment and will educate Belfood products that use raw materials from Sieradâs best quality chicken. WO Strategies to conduct a campaign through the Internet and social networking, improve promotion, especially in young children, in order to build brand awareness in young people and conduct training of human resources. WT Strategies to improve product quality and improve service to consumers and users. PT. Belfoods Indonesia should choose Strategy Focus on Low Cost (or market niche strategy focused on low-cost), where this strategy focuses on a narrow segment of buyers (selling a product / brand among consumers who fit the target) and won the competition by offering products with lowest cost compared to competitors. This can be done, because Belfoods use raw materials from raw chicken from Sierad Produceâs Chicken Slaughterhouse which is the highest quality farmed.